Herramientas virtuales y su incidencia en la comunicación digital de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2021 - Barahona Campuzano, Adrian Alexander (2022)
The use of new digital communication technologies has influenced to facilitate, facilitate their educational development, on the proper use of virtual tools, which allow the development of cognitive skills and abilities based on collaborative learning and participatory action, with telematic applications, in which the computers that facilitate the sending and receiving of data interact. The objective of this project is to determine the incidence of virtual digital communication tools of the Technical University of Babahoyo Extension Quevedo, Year 2021. The research process was developed by applying the survey technique through which a questionnaire of questions was carried out. in relation to the research topic where it was addressed with questions about virtual tools and their impact on digital communication. Concluding that virtual tools are useful for the development of educational processes at the Technical University of Babahoyo, which allows them a more active, participatory education, interacting with teachers and students, as well as sharing information immediately, promoting significant learning and improving each one of the processes that take place.